Design of an Automatic Temperature and Humidity Control System Prototype for Rice Seedling Nursery - Siswoyo Soekarno; Dwi Wahyu Widarman; Bayu Taruna Widjaja Putra; Tasliman Tasliman (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Temperature and humidity control in rice nurseries is carried out to maintain the quality of rice seeds and avoid planting failure. Control is carried out using a prototype automatic device equipped with a water pump for watering and a mist maker plus a fan for humidifying. Based on observations, the prototype tool operates according to the given program. The water pump will turn on when the time shows 07:00 a.m. and 02:00 p.m. Meanwhile, the mist maker plus fan will turn on according to the regulated temperature and humidity conditions and can be applied to several regions in Indonesia. However, at the research site it will turn on when the temperature is > 27 °C and the humidity is < 70% and will turn off when the temperature reaches 27 °C and the humidity is 86%. The optimal air temperature for rice growth ranges from 19–27 °C with humidity in the RH range of 70–86%. Observations were carried out in two treatments, namely conditions with control and conditions without control. The results of seedling with control are better than without control. This can be seen from the growth of rice seedlings with control having a higher value than rice seedlings without control.